Frontiers of cancer care in Asia-Pacific region: cancer care in Australia - Koh, ES (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2008)
Cancer has a significant impact on the Australian community. One in three men and one in four women will develop cancer by the age of 75. The estimated annual health expenditure due to cancer in 2000-1 in Australia was $2.7 billion, representing 5.5% of the country’s total healthcare expenditure. An historical overview of the national cancer control strategies in Australia is provided. In males, the five most common cancers in order of decreasing incidence are: prostate cancer, colorectal cancer, lung cancer, melanoma and lymphoma, while for Australian women, breast cancer is the most common cancer. Key epidemiologic information about these common cancers, current management issues and comprehensive national clinical practice guidelines (where available) are highlighted. Aspects of skin cancer, a particularly common cancer in the Australian environment – with a focus on melanoma – are also included. Cancer outcomes in Australia, measured by selected outcomes, are among the best in the world. However, there is still evidence of health inequalities, especially among patients residing in regional and remote areas, the indigenous population and people from lower socio-economic classes. Limitations of current cancer care practices in Australia, including provision of oncology services, resources and other access issues, as well as suggested improvements for future cancer care, are summarised. Ongoing implementation of national and state cancer control plans and evaluation of their effectiveness will be needed to pursue the goal of optimal cancer care in Australia.